Perlindungan Konsumen Pada Produk Pembiayaan Syariah Berbasis Aplikasi: Konstruksi Hukum Di Era Digital - Purba S, Yevanya Sagita; B, Baidhowi (Media Hukum Indonesia (MHI), 2025)
Digital transformation in the Islamic financial sector through the use of technology-based financing applications presents new dynamics in the legal relationship between business actors and consumers. This study aims to construct a legal protection model for consumers in the use of digital Islamic financing products, with a normative legal approach based on national laws and regulations, fatwas of the National Sharia Council–Indonesian Ulema Council (DSN–MUI), and the principles of Islamic economic law. The findings show that existing regulations are still partial and have not fully accommodated the complexity of application-based transactions, especially in terms of transparency of contracts, protection of personal data, and dispute resolution mechanisms. Therefore, integration between positive legal norms and the values of maqāṣid al-sharī‘ah is needed in order to realize a consumer protection system that is fair, proportional, and in accordance with the characteristics of Islamic finance in the digital era. Regulatory harmonization and strengthening of supervisory authorities are the main pillars in realizing legal certainty